ANALISIS MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN DAMPAKNYA TERHADAP KEPATUHAN WAJIB PAJAK DALAM PERSPEKTIF ADMINISTRASI NEGARA - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2025)
This study analyses the modernisation of the tax administration system in Indonesia through the implementation of e-Filing, e-Billing, e-Registration, and the Coretax System, as well as its impact on taxpayer compliance from a state administration perspective. Using a literature review method, the study found that digital transformation successfully increased the ratio of annual tax return submissions from 65 per cent to 92 per cent and the tax-to-GDP ratio to 11.8 per cent through reduced compliance costs, real-time transparency, and AI-based risk analysis. From a state administration perspective, this modernisation embodies the principles of good governance and New Public Management by building public trust, although the challenges of the digital divide and technological literacy require inclusive mitigation for the sustainability of positive impacts. The results of the study provide policy recommendations for the Directorate General of Taxes in strengthening national digital bureaucratic reform.